The European Higher Education Area Faces Its Fundamental Values - Bergan, Sjur (International Higher Education, 2022)
Backsliding of democracy puts the values of the European Higher Education Area (EHEA) under pressure. The EHEA finds it difficult to deal with violations. Higher education leaders must debate issues that do not make headlines as well as those that do. They must demonstrate international solidarity, so that higher education systems in vulnerable countries receive support as they deserve and need. The EHEA must focus on a fundamental values program for the decade until 2030.